Safety and efficacy of sintilimab versus pembrolizumab in the treatment of advanced or recurrent pediatric malignancies: a real-world study in China - Mao, Lei; Li, Mengzhen; Wu, Linnan; Wang, Juan; Que, Yi; Sun, Feifei; Huang, Junting; Lu, Suying; Zhen, Zijun; Zhu, Jia; Song, Mengjia; Zhang, Yizhuo (Frontiers in Immunology, 2025)
BackgroundProgrammed death receptor 1 (PD-1) inhibitors have shown durable response and mild adverse events in adult malignancies. However, study on PD-1 inhibitors in pediatric patients remains limited, and a direct comparison of distinct PD-1 inhibitors in pediatric tumors is lacking.MethodsWe conducted a retrospective analysis of 75 pediatric patients with advanced or recurrent malignancies treated with either Sintilimab-based (n=53) or Pembrolizumab-based (n=22) regimens. The primary endpoints included treatment-related adverse events (TRAEs) and objective response rate (ORR), and the second endpoints included progression-free survival (PFS) and overall survival (OS).ResultsThe incidence of hypothyroidism, hyperthyroidism, pneumonia, increased ALT/AST, gastroenteritis, and rash following immune checkpoint inhibitor therapy showed no significant differences between the Sintilimab group and the Pembrolizumab group (all P>0.05). Cardiovascular Adverse Events (CVAEs) occurred in 26.0% (15/53) of Sintilimab-treated patients versus 40.0% (8/20) of Pembrolizumab-treated patients (P=0.26). In the lymphoma cohort (n=13), 88.9% of Sintilimab-treated patients and 75.0% of Pembrolizumab-treated patients achieved complete response (CR) or partial response (PR) (P=0.54). The median PFS and OS were not reached in either group. In the non-lymphoma cohort (n=53), 40.5% of Sintilimab-treated patients and 25.0% of Pembrolizumab-treated patients achieved CR or PR (P=0.18). Among 39 patients who had received ≤ 2 prior treatment lines, the PFS and OS showed no significant differences between the Sintilimab (n=30) and Pembrolizumab (n=9) groups (P=0.28 and P=0.09, respectively). Similarly, among 14 patients who had received>2 prior treatment lines, no significant differences in PFS and OS were observed between the Sintilimab(n=7) and Pembrolizumab(n=7) groups (P=0.33 and P=0.15, respectively).ConclusionsSintilimab demonstrated favorable tolerability and efficacy in pediatric patients with malignancies, with a safety and efficacy profile comparable to Pembrolizumab. For pediatric patients with advanced or recurrent malignancies receiving immune checkpoint inhibitor therapy, long-term monitoring of thyroid and cardiac function is recommended.